The Evolution of Currency: Bridging Traditional Banking and Cryptocurrency with TNT - Haykov, Joseph Mark (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
Transparent Network Technology (TNT) merges established banking practices with Decentralized Finance (DeFi), prioritizing the reduction of asymmetric information through increased transparency. Unlike the continuous, real-time processing typical in cryptocurrencies such as Bitcoin, TNT adopts a batch processing approach similar to that traditionally used by banks, where transactions are accumulated throughout the day and processed overnight. This method, employed by banks since the Italian Renaissance, significantly enhances both efficiency and security. We highlight how TNT utilizes the Nash equilibrium concept from game theory to ensure transaction integrity and mitigate prevalent risks such as double-spending in decentralized systems. Furthermore, we explore the legal ramifications of integrating dual signatures in TNT-bank transactions, an additional advantage of batch processing, which establishes these transactions as legally enforceable contracts. By critiquing the limitations of Bitcoin’s framework and illustrating the enhanced capabilities of TNT, we advocate for a paradigm shift in cryptocurrency practices to better align with those of traditional banks, suggesting a model that could redefine money.